Electronic companies and their legal nature - Zeina Ghanem Abdul Jabbar Al Saffar (الرافدین للحقوق, 2009)
E-commerce was established in general at the end of the last century and occupied a prominent place in the international arena as a modern method of trade to bring the views of the contractors and conduct negotiations and the conclusion of transactions and contracts that take place over the Internet.